The Influence Of Promotion And Word Of Mouth On The Decision To Choose An International Kaniva Job Training Institution Through Brand Image As A Mediation Variable - Handayani, Ni Putu Lely; Joko Adinegara, I Gusti Ngurah; Komalasari, Yeyen; Purnama Trimurti, Christimulia (The Es Economics and Entrepreneurship, 2024)
This study aims to understand how promotion and word of mouth affect consumer perceptions of Kaniva International's brand image, as well as how these perceptions influence consumer decisions in choosing this training institution. The study used a quantitative approach with an associative research design and involved 72 respondents as samples. Data collection techniques include questionnaires, interviews, observations, and literature studies. Data analysis was conducted using Partial Least Square (PLS), a variant-based structural equation model. The results showed that promotion and word of mouth have a positive influence on the decision to choose LPK Kaniva International and also on its brand image. Brand image also has a positive effect on the decision to choose Kaniva International. In addition, promotion and word of mouth influence the decision to choose Kaniva International through brand image mediation, suggesting that effective promotion strategies and word of mouth recommendations can improve brand image perceptions and influence consumer decisions.